2002
DOI: 10.1242/jeb.205.2.253
|View full text |Cite
|
Sign up to set email alerts
|

The archaeogastropod molluscHaliotis iris: tissue and blood metabolites and allosteric regulation of haemocyanin function

Abstract: SUMMARY We investigated divalent cation and anaerobic end-product concentrations and the interactive effects of these substances and pH on haemocyanin oxygen-binding (Hc-O2) in the New Zealand abalone Haliotis iris. During 24 h of environmental hypoxia (emersion), d-lactate and tauropine accumulated in the foot and shell adductor muscles and in the haemolymph of the aorta, the pedal sinus and adductor muscle lacunae, whereas l-lactate was not detected. Intramuscular and haemolymph d-lactate conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Hemocyanin concentration was estimated according to the method described by Behrens et al [ 30 ]. Fresh blood was diluted 30-fold in buffer (glycine 50 mM, EDTA 10 mM, pH 8.8), and absorbance was measured with a spectrophotometer at 346 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Hemocyanin concentration was estimated according to the method described by Behrens et al [ 30 ]. Fresh blood was diluted 30-fold in buffer (glycine 50 mM, EDTA 10 mM, pH 8.8), and absorbance was measured with a spectrophotometer at 346 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Haemocyanin level was then determined from the absorbance at 346 nm using the Unicam 8625 UV/Vis spectrophotometer with a D2 lamp. Haemocyanin concentrations (Hcy) were calculated using a practical extinction coefficient determined from copper analysis (E mM Hcy, 1 cm = 22.84 for millimolar Hcy measured in a 1-cm cuvette) (Behrens et al 2002;Ragg and Taylor 2006):…”
Section: Haemocyanin Concentration and Haemolymph Proteinmentioning
confidence: 99%
“…In molluscs, haemocyanin transports oxygen and assists in immune responses (Jaenicke et al 2009). Elevating temperature can raise haemocyanin to transport more oxygen to the tissue, thus increasing haemolymph protein (Behrens et al 2002;Giomi and Pörtner 2013). Lu et al (2016) found that temperature affected both haemolymph sodium and potassium concentrations of the gazami crab (Portunus trituberculatus).…”
Section: Introductionmentioning
confidence: 99%